Interface automatic adjustment according user features (Research, Society and Development, 2020)
The human-computer graphical user interface project requires identify the characteristics of users. An interface that fits - considering the needs and desires of each individual user - may be more effective to their goals. This study aims to determine the effectiveness of a human-computer interface that automatically adapts to the user profile. The concepts and theories involving Adaptive Interface systems were investigated, highlighting the studies in web morphing. Based on these studies, a test was developed, simulating a multimedia Learning Objects adaptive interface in order to collect data about user behavior on the interface adaptation. Analysis of the data generated results regarding the characteristics of participants as to the preferences and performance on the test. It was measured relationships between data, where the influences between the variables in the results are addressed.